An injectable 2.5% cross-linked polyacrylamide hydrogel (2.5 iPAAG) demonstrates no neurotoxicity in human induced pluripotent stem cells-derived iCell® GlutaNeurons - Walmod, Peter S.; Kusk, Philip; Jøhnk, Nina; Ankorina-Stark, Ieva; Essex, Anthony (Frontiers in Toxicology, 2025)
IntroductionArthrosamid®, Arthramid®, Bulkamid®, and Mictamid® are products for the management of osteoarthritis and female urinary incontinence. All four products include the same injectable hydrogel consisting of 2.5% crosslinked polyacrylamide termed 2.5 iPAAG that is polymerized from the neurotoxic compound acrylamide.MethodsTo investigate whether 2.5 iPAAG demonstrates any neurotoxic effects in vitro, human iCell® Glutaneurons were exposed to concentrations of up to 20% (w/w) 2.5 iPAAG for up to 96 h. Cells were stained and recorded by fluorescence microscopy for the subsequent estimation of cell survival, cell death, apoptosis, and the formation and maintenance of the neurite network.ResultsThe negative control, Fish Gelatin, did not affect cell survival, cell death, or apoptosis, and had no or minor effects on the neurite network area. The positive controls acrylamide and A23187 caused a pronounced time- and dose-dependent decrease in cell survival, an increase in cell death, but not apoptotic cell death, and a strong decrease in neurite network area, whereas another positive control, Tunicamycin, caused a time- and dose-dependent increase in cell death and apoptosis but only a minor decrease in the average neurite network area. At the tested concentrations and timepoints, the 2.5 iPAAG had no statistically significant effects on cell survival, non-apoptotic and apoptotic cell death, or the neurite network area.DiscussionThese results support the interpretation that 2.5 iPAAG demonstrates no apparent in vitro neurotoxic or cytotoxic effects in human iCell® Glutaneurons when included in cell cultures at concentrations of up to 20% (v/v) for up to 96 h.